User localisation using wireless signal strength - an application for pattern classification using fuzzy decision tree. (2016) - Narayanan, Swathi Jamjala; Bhatt, Rajen B.; Paramasivam, Ilango
Due to prevalent availability of wireless networks, there is enormous usage of mobile devices among the public in all sectors. Locating the mobile devices using the wireless signal strength received enables transparent and immediate services for both indoor and outdoor users. For indoor users, a smart environment could be provided by giving smart facilities like automating switching on/off of room lights, air conditioning, etc., by finding the user's exact location using their mobile device. Similarly, outdoor users can get services from the mobile service providers based on their current location. In this paper, we consider indoor user localisation as a pattern classification problem and propose to apply fuzzy decision tree (FDT) for locating users. As far as our knowledge is concerned, this is the first attempt to apply FDT for locating users in indoor environment using wireless signal strength received by user's handheld devices.